The Effect of Security, Speed, and Ease on Customer Loyalty to E-Wallets on the Marketplace Platform - Memed Hasan (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study examines the effects of security, transaction speed, and ease of use on customer loyalty in the context of e-wallet usage within Indonesian marketplace platforms. As digital payment systems continue to gain traction, understanding the factors that influence customer loyalty is crucial for e-wallet providers. The research is based on the Technology Acceptance Model (TAM) and ES-QUAL, using data from 119 respondents, primarily students aged 21–25. The measurement instruments used in the study were confirmed to be valid and reliable, with item-total correlation values exceeding the critical threshold and Cronbach’s Alpha values above 0.743. The data met the assumptions for normality, with no issues of multicollinearity or autocorrelation, although heteroscedasticity was observed in the security variable. Using multiple linear regression analysis, the study found that all three variables—security, transaction speed, and ease of use—significantly affected customer loyalty. Ease of use had the highest impact (β = 0.280, p = 0.001), followed by security (β = 0.284, p = 0.001), and transaction speed (β = 0.228, p = 0.007). The regression model explained 33.7% of the variation in customer loyalty (R² = 0.337). These findings highlight the importance of creating user-friendly interfaces, ensuring fast and efficient transactions, and providing strong data protection in building customer loyalty. Recommendations for e-wallet providers and policymakers include enhancing service quality and promoting broader adoption of digital financial services.